2018
DOI: 10.12659/msm.910214
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic Activity of Wrap53 in Human Colorectal Cancer In Vitro and in Nude Mouse Xenografts

Abstract: BackgroundWD40-encoding RNA antisense to p53 (Wrap53) has been implicated in cancer development. However, the role of Wrap53 remains unknown in colorectal cancer. The aim of this study was to elucidate the function of Wrap53 in colorectal cancer tumorigenesis and development.Material/MethodsThis study analyzed Wrap53 expression in colorectal cancer tissue specimens using The Cancer Genome Atlas data and tumor cell lines and assessed the effects of Wrap53 knockdown on regulation of cancer cell malignant phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…1 ). (1) Intergenic lncRNAs originate from DNA sequences between two protein-coding genes, such as MALAT1 13 , Linc-ROR 14 , and ANCR 15 ; (2) intronic lncRNAs originate from introns of protein-coding genes, such as PRUNE2 16 , PCA3 17 , COLDAIR 18 , and SYISL 19 ; (3) sense lncRNAs overlap with one or more introns and exons of different protein-coding genes, such as LncRNA-GAS5 13 and ecCEPBA 20 ; (4) antisense lncRNAs originate from an opposite direction to a protein-coding gene, such as TALAM1 21 , PDCD4-AS1 22 , and Wrap53 23 ; (5) enhancer lncRNAs originate from the regions of promoter enhancer, such as LncRNA-LEENE 24 and Lnc-SLC4A1-1 25 ; and (6) bidirectional lncRNAs exist in proximity of a coding transcript of the opposite strand, such as Linc00441 26 and Catsper1au 27 . So far, lncRNAs have been shown to exert auxiliary functions either to tumor suppression or to tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…1 ). (1) Intergenic lncRNAs originate from DNA sequences between two protein-coding genes, such as MALAT1 13 , Linc-ROR 14 , and ANCR 15 ; (2) intronic lncRNAs originate from introns of protein-coding genes, such as PRUNE2 16 , PCA3 17 , COLDAIR 18 , and SYISL 19 ; (3) sense lncRNAs overlap with one or more introns and exons of different protein-coding genes, such as LncRNA-GAS5 13 and ecCEPBA 20 ; (4) antisense lncRNAs originate from an opposite direction to a protein-coding gene, such as TALAM1 21 , PDCD4-AS1 22 , and Wrap53 23 ; (5) enhancer lncRNAs originate from the regions of promoter enhancer, such as LncRNA-LEENE 24 and Lnc-SLC4A1-1 25 ; and (6) bidirectional lncRNAs exist in proximity of a coding transcript of the opposite strand, such as Linc00441 26 and Catsper1au 27 . So far, lncRNAs have been shown to exert auxiliary functions either to tumor suppression or to tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that WRAP53β was a potential oncoprotein, whose overexpression led to transformation and promoted cancer cell survival, and whose downregulation induced massive cell death [29][30][31][32]. In addition, overexpression of WRAP53β was related to NSCLC progression.…”
Section: Discussionmentioning
confidence: 97%
“…Loss of WRAP53β is associated with poor prognosis in head and neck (26), breast (27) and ovarian cancer (28), suggesting a tumour suppressor role (29,30). Although upregulation of WRAP53β has also been reported in cancer, correlation with patient survival has been inconsistent (31)(32)(33). Instead, this upregulation, which is known to occur in precancerous lesions, may reflect WRAP53β involvement in DNA repair in order to constrain tumour progression (29,30).…”
Section: Evaluation Of Dyskerin Expression and The Cajal Body Protein Wrap53β As Potential Prognostic Markers For Patients With Primary Vmentioning
confidence: 99%